2022
DOI: 10.1155/2022/7102500
|View full text |Cite|
|
Sign up to set email alerts
|

Network Pharmacology-Based Strategy to Investigate the Mechanisms of Lenvatinib in the Treatment of Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a complex and refractory malignant tumor, ranking the third cause of cancer-related deaths worldwide. Lenvatinib is currently employed to treat advanced, unresectable HCC as a first-line drug. The purpose of this study was to explore the pharmacological mechanisms of lenvatinib acting on HCC through the analysis of differential expressed genes based on network pharmacology. The target genes of lenvatinib were collected from PubChem, SwissTargetPrediction, PharmMapper, and BATM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Lenvatinib is one of the first-line oral multikinase inhibitors for advanced HCC, targeting vascular endothelial growth factor receptor 1-3 (VEGFR1-3), fibroblast growth factor receptor 1-4 (FGFR1-4), platelet-derived growth factor receptor alpha (PDGFRA), KIT proto-oncogene, receptor tyrosine kinase (KIT), and rearranged during transfection (RET). 123,124 In the study, docking algorithms were used to predict the non-covalent interaction between molecular targets and the drug identifying AURKA as one of the possible targets of lenvatinib in HCC. 123 Over the years, various studies identified several compounds able to inhibit AURKA in vitro, with some accumulating sufficient evidence to undergo further evaluation as potential cancer therapies during preclinical or clinical trials.…”
Section: Targeting Aurka For Liver Cancer Therapymentioning
confidence: 99%
See 3 more Smart Citations
“…Lenvatinib is one of the first-line oral multikinase inhibitors for advanced HCC, targeting vascular endothelial growth factor receptor 1-3 (VEGFR1-3), fibroblast growth factor receptor 1-4 (FGFR1-4), platelet-derived growth factor receptor alpha (PDGFRA), KIT proto-oncogene, receptor tyrosine kinase (KIT), and rearranged during transfection (RET). 123,124 In the study, docking algorithms were used to predict the non-covalent interaction between molecular targets and the drug identifying AURKA as one of the possible targets of lenvatinib in HCC. 123 Over the years, various studies identified several compounds able to inhibit AURKA in vitro, with some accumulating sufficient evidence to undergo further evaluation as potential cancer therapies during preclinical or clinical trials.…”
Section: Targeting Aurka For Liver Cancer Therapymentioning
confidence: 99%
“…123,124 In the study, docking algorithms were used to predict the non-covalent interaction between molecular targets and the drug identifying AURKA as one of the possible targets of lenvatinib in HCC. 123 Over the years, various studies identified several compounds able to inhibit AURKA in vitro, with some accumulating sufficient evidence to undergo further evaluation as potential cancer therapies during preclinical or clinical trials. The initial generation of AURKA inhibitors comprises ATP-competitive inhibitors that bind to the ATP binding pocket of AURKA, and currently represent the majority of AURKA inhibitors that have undergone clinical investigation.…”
Section: Targeting Aurka For Liver Cancer Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Tis article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%